2020
DOI: 10.1002/smi.3010
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial safety climate and stigma: Reporting stress‐related concerns at work

Abstract: While researchers have begun to investigate theory and methods related to attenuating stress‐related issues at work, one underexplored area is a barrier to reporting stress‐related concerns in the workplace. Research on organizational climate broadly covers psychosocial safety at work. However, the literature has not examined other, more specific factors such as stigma towards reporting stress‐related concerns in the workplace. Using a prospective design, the current study examined the distinction between psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
1
4
0
2
Order By: Relevance
“…Previous research has shown that a negative work climate in the organisation can lead to the underreporting of stress-related issues due to fear of it having a negative impact on one's work relationships. Furthermore, structural issues at work can negatively affect workers' willingness to discuss work-related stress, potentially leading to bullying or burnout [40]. Another stressor in line with our results is organisation-imposed work overload due to the lack of individually altering responsibilities and duties based on personal needs and preferences.…”
Section: Discussionsupporting
confidence: 79%
“…Previous research has shown that a negative work climate in the organisation can lead to the underreporting of stress-related issues due to fear of it having a negative impact on one's work relationships. Furthermore, structural issues at work can negatively affect workers' willingness to discuss work-related stress, potentially leading to bullying or burnout [40]. Another stressor in line with our results is organisation-imposed work overload due to the lack of individually altering responsibilities and duties based on personal needs and preferences.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, PSC has the capacity to reduce the impact of workplace bullying on post-traumatic disorder and work engagement [ 12 , 44 ] Kwan et al [ 39 ] revealed that the positive association between bullying and neglect is diminished when a high PSC is perceived by workers. Moreover, PSC moderates the associations between role conflict and workplace bullying [ 17 ], role ambiguity and workplace bullying [ 17 ] and stigma and workplace bullying [ 15 ]. While a limited research attention is given, a study reported that PSC mediates the association between health-centric leadership and workers’ psychological health problems [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fevre et al [ 15 ] noted that short, direct bullying questions, such as the stem question used on the APMS, may risk some types of negative workplace behaviours of interest not being reported. Underreporting may also have occurred for various reasons, including stigma [ 59 ], lack of recognition/agreement that a behaviour was bullying [ 60 ], patterns of non-response, and the exclusion of those not in paid work in the past month [ 61 ]. Risk of selection bias is also a limitation of the current study.…”
Section: Discussionmentioning
confidence: 99%